Обзор голубянок группы Lycaena phoenicurus (Lepidoptera, Lycaenidae) с описанием нового вида из Азербайджана - Некрутенко, Ю.П.; Эффенди, Р.М.Э. (Вестник зоологии, 1983)
The species group that dropped out of the genus Hyrcanana Bethune-Baker after restriction of its taxonomic content is reviewed (cf. Nekrutenko, 1983). All species considered are assigned to Lycaena s.I. It is found that Polyommatus phoenicurus margelanica Staudinger, 1881 sirongly distinctive by male and female genitalic characters from all other phoenicurus-like species and elevated fo the species rank level was confused with and wrongly named as L. phoenicurus in the type designation of Phoenicurusia Verity, 1943; at the same time, the genitalic characters of L. phoenicurus, established after topolype examination, appear to be identic with those used as diagnostic for Athamanthia Zhdanko, 1983, established for L. athamantis (Ev.) L. phoenicurus scintillans (Christoph, 1887) and L. phoenicurus transcaucasica (Miller, 1923) are sunk in synonymy of L. phoenicurus phoenicurus (Lederer, 1872). Lectotype female and paralectotype females of Polyommatus athamantis Eversmann, 1854 are designated of ten Eversmann’s syntypes (Zoological Institute, USSR Academy of Sciences, Leningrad). L. japhetica_sp. n.— differs from all other species of the phoenicurus-group by large diffused whitish fields on the wings upper side. Type locality: Azerbaijan SSR, Apsheron, Tazakend, Dizavar-cay river valley. Type material: ‘18 males and 11 females are deposited at the Insfitute of Zoology, Ukr.SSR Academy of Sciences (including holotype), Institute of Zoology, Azerbaijan SSR Academy of Sciences (Baku), Zoological Institute, USSR Academy of Sciences (Leningrad) and in the British Museur (Natural History).